Overset DNS with application to homogeneous decaying turbulence - Rinie A. D. Akkermans and Nadine Buchmann and Jürgen Dierke and Roland Ewert (Notes on numerical fluid mechanics and multidisciplinary design, 2016)
In this contribution an application of a computational aeroacoustics code as a hybrid Zonal DNS tool is presented. The derivation of the Non-Linear Perturbation Equations (NLPE) extended with viscous terms is shown as well as information related to the numerical method is given. The application of the simulation tool to a generic three-dimensional test case, i.e., the Taylor-Green Vortex (TGV), is presented. This TGV, initially consists of only one length scale, develops into homogeneous decaying turbulence. Results of energy spectrum and grid convergence study are given. It is shown that the observed accuracy of the numerical code matches well with the expected theoretical order of four.